Reconsidering the function of the xyloglucan endotransglucosylase/hydrolase family - Ishida, Konan; Yokoyama, Ryusuke (Journal of plant research, 2022)
Plants possess an outer cell layer called the cell wall. This matrix comprises various molecules, such as polysaccharides and proteins, and serves a wide array of physiologically important functions. This structure is not static but rather flexible in response to the environment. One of the factors responsible for this plasticity is the xyloglucan endotransglucosylase/hydrolase (XTH) family, which cleaves and reconnects xyloglucan molecules. Since xyloglucan molecules have been hypothesised to tether cellulose microfibrils forming the main load-bearing network in the primary cell wall, XTHs have been thought to play a central role in cell wall loosening for plant cell expansion. However, multiple lines of recent evidence have questioned this classic model. Nevertheless, reverse genetic analyses have proven the biological importance of XTHs; therefore, a major challenge at present is to reconsider the role of XTHs in planta . Recent advances in analytical techniques have allowed for gathering rich information on the structure of the primary cell wall. Thus, the integration of accumulated knowledge in current XTH studies may offer a turning point for unveiling the precise functions of XTHs. In the present review, we redefine the biological function of the XTH family based on the recent architectural model of the cell wall. We highlight three key findings regarding this enzyme family: (1) XTHs are not strictly required for cell wall loosening during plant cell expansion but play vital roles in response to specific biotic or abiotic stresses; (2) in addition to their transglycosylase activity, the hydrolase activity of XTHs is involved in physiological benefits; and (3) XTHs can recognise a wide range of polysaccharides other than xyloglucans.